Phisical Function (Motor Activity) Pada Pasien Kritis Dengan Sedation Di Intensive Care Unit - Heru Suwardianto; Awal Prasetyo; Reni Sulung Utami (coba, 2017)
Introduction: Critical patients are patients who potentially get reversible dysfunction in one or more life-threatening organs and require they require care in the Intensive Care Unit (ICU). Method: The objective of this research is to analyze the physical function-tardive dyskinesia on critical patients with sedation in ICU. The design of this research is crossectional. The population is all critical patients in ICU Baptist Hospital Kediri. The sample is 41 respondents based on the inclusion and exclusion criteria in the total sampling. The independent variable is giving the sedation and the dependent variable is physical function-tardive dyskinesia. The data was collected using observation sheets. Result: The result shows that giving a sedation can decrease the physical function in the form of motor activity; response of noxious stimuli (7.3%), response to touch or calling name (19,5%) and the incresing score of agitation and co-operative (4.9%). Symptoms of tardive dyskinesia increased after sedation in the form of tongue prostrusion (4.9%), lip smacking puckering and pursing (2.4%), and rapid movements of the arms and legs. Administration of sedation in the first 24-hour ICU patient affects the physical function of the critical patients (p = 0.005). Conclusion: Giving sedation affects the change of patiens’ physical funcion. Therefore, prevention on the effects of sedation and treatment during ICU is needed in order to avoid a decrease in the physical function of critical patients. Keyword: physical function, tardive dyskinesia, sedation, critical patient, ICU